2021
DOI: 10.35808/ersj/2075
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Assessment of Seniors on the Phenomenon of Discrimination: Analysis Against the Background of the Europe 2020 Strategy Implementation

Abstract: Purpose: Our study aimed to compare objective factors increasing discrimination and subjective feelings of seniors about discrimination. Additionally, we have attempted to indicate whether the elderly is discriminated against and to what extent they report such situations. Design/Methodology/Approach: The linear ordering by Hellwig's method was used to construct Taxonomic Measure of Preventing Exclusion (TMPEi) and synthetic measures for finding the level of discrimination perception by seniors. Eurostat data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In our study, we focused on activities undertaken or activity assessments made by seniors aged 65+. There is some debate in the literature about what age should be used to define old age [82][83][84][85][86][87]. However, according to Alén et al [86] and Przybysz et al [87], we accept the age limit of 65 as older elderly.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we focused on activities undertaken or activity assessments made by seniors aged 65+. There is some debate in the literature about what age should be used to define old age [82][83][84][85][86][87]. However, according to Alén et al [86] and Przybysz et al [87], we accept the age limit of 65 as older elderly.…”
Section: Methodsmentioning
confidence: 99%
“…The ages used to identify senior citizen tourists vary depending on the country and the socioeconomic conditions under consideration. Przybysz et al [ 25 ] found that an officially older adult is a person over 60 years of age, but in the Central Statistical Office of Poland studies, one can find a reference to Eurostat and OECD, in which the term elderly is used for people over 65.…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
“…When they participate in recreation and tourism they overcome (reasonably) their own limitations, which may bring additional benefits. Accordingly, it is clear that the concept of ageism has an essential meaning for analysing discrimination against seniors [ 25 ]. In creating his definition of ageism in 1969, Butler [ 29 ] intended to present a number of factors focusing on prejudices against the elderly.…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: Socially engaged arts; outcomes; presentation of results; data visualisation, documentation Despite the rapid social development and recognition of fundamental human rights over the past few decades in most parts of the world (Beitz, 2011;Streeten, 1981;United Nations General Assembly, 1949), a large body of evidence consistently has demonstrated widespread discrimination towards people with specific personal and sociodemographic characteristics (Arrow et al, 2015). A large number of studies in Europe and other countries have also demonstrated widespread discrimination (EU-MIDIS, 2010, 2017), most frequently based on ethnic or immigrant origin (Esses, 2021;Kende et al, 2021), gender (Cleveland et al, 2013;Bobbitt-Zeher, 2011), sexual orientation (Patacchini et al, 2015;Przybysz et al, 2021), religious beliefs (Evans, 2012) and disability (Hackett et al, 2020).…”
Section: Introductionmentioning
confidence: 99%